2017
DOI: 10.1111/tpj.13728
|View full text |Cite
|
Sign up to set email alerts
|

CLD1/SRL1 modulates leaf rolling by affecting cell wall formation, epidermis integrity and water homeostasis in rice

Abstract: Leaf rolling is considered as one of the most important agronomic traits in rice breeding. It has been previously reported that SEMI-ROLLED LEAF 1 (SRL1) modulates leaf rolling by regulating the formation of bulliform cells in rice (Oryza sativa); however, the regulatory mechanism underlying SRL1 has yet to be further elucidated. Here, we report the functional characterization of a novel leaf-rolling mutant, curled leaf and dwarf 1 (cld1), with multiple morphological defects. Map-based cloning revealed that CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 62 publications
(107 reference statements)
4
52
0
Order By: Relevance
“…It provides mechanical support to plants by increasing cell wall hardness and enhancing compressive strength of cells [60][61][62]. We found that repressing the expression level of Gh4CL7 in G. hirsutum reduced the lignin content and led to a reduction in drought resistance, consistent with the result of rice plants with a decreased lignin content being more prone to drought stress [63]. Studies in Fraxinus mandshurica also showed that decreased lignin content resulted in drought resistance reduction [24].…”
Section: Discussionsupporting
confidence: 79%
“…It provides mechanical support to plants by increasing cell wall hardness and enhancing compressive strength of cells [60][61][62]. We found that repressing the expression level of Gh4CL7 in G. hirsutum reduced the lignin content and led to a reduction in drought resistance, consistent with the result of rice plants with a decreased lignin content being more prone to drought stress [63]. Studies in Fraxinus mandshurica also showed that decreased lignin content resulted in drought resistance reduction [24].…”
Section: Discussionsupporting
confidence: 79%
“…Drought‐tolerant maize inbred lines under drought stress conditions display higher lignification than drought‐sensitive inbred lines (Hu et al ., ). Also, the curled leaf and dwarf 1 ( cd1 ) mutant exhibit significant decrease in lignin contents in secondary cell walls causing water deficits in cd1 leaves and resulting to reduced drought tolerance (Li et al ., ). In addition, reduced lignification in plants increases their xylem vulnerability to embolism (Voelker et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Regulation of stomatal movement in this regard has been an active research area for drought tolerance. For example, overexpression of OsASR5 , ONAC022 , AtMYB61 , BplMYB46 and PtoMYB170 significantly enhanced drought tolerance in plants by regulation of stomatal closure under drought stress conditions (Guo et al ., ; Hong et al ., ; Li et al ., ; Romano et al ., ; Xu et al ., ). Interestingly, overexpression of AtMYB61 , BplMYB46 and PtoMYB170 also increased lignin biosynthesis.…”
Section: Introductionmentioning
confidence: 98%
“…T-DNA insertion in OsBC1L4 results in abnormal cell expansion, dwarfing, and fewer tillers in rice [25]. The CLD1/SRL1 gene encodes a GPI-anchored membrane protein that modulates leaf rolling and other aspects of rice growth and development [26,27].…”
Section: Introductionmentioning
confidence: 99%